FACTORS AFFECTING THE LEARNING READINESS OF PRIMARY STUDENTS TO ONLINE INSTRUCTION DURING COVID-19 PANDEMIC - Kumsawai , Rattanaporn; Nuangchalerm, Prasart; Sriwarom , Napaporn; Kalasin, Chaemchan Na (International Online Journal of Education and Teaching, 2022)
Current classroom has been transformed by the pandemic into a new normal of learning and online education, with students learning to participate in online classrooms. The research aims to explore the factors affecting the learning readiness of grade 4-6 students to online instruction during COVID-19 pandemic. One hundred students from one school in Khon Kaen province, Thailand provided information and express opinion towards factors affecting the learning readiness. Questionnaire of factors that influence students' readiness to attend online teaching and learning was used. In the situation of the COVID-19 pandemic, data were collected through online surveying. Statistics used to analyze data were descriptive statistics, percentage, mean, and standard deviation. Overall, the factors affecting the learning readiness by mean of student is at moderately readiness, parental factor is at moderately readily available, but the school supplies factor is high readily available.